Midwife’s professional functions prescribed by the law - Iwanowicz-Palus, Grażyna Jolanta; Krysa, Justyna; Korżyńska-Piętas, Magdalena; Rzońca, Ewa; Bień, Agnieszka (Polish Journal of Public Health, 2018)
A midwife is an independent medical profession regulated by law. It is treated as a mission, a profession of public trust. The independence of midwife expresses in the professional activities which are performed in accordance with professional competences. Moreover, it is a universal feature of the midwife profession. International and national regulations are important in process of shaping the legal status of the midwife profession. Due to its nature, this profession requires from the midwives continuous, lifelong learning and professional improvement. National and European legislation on midwife profession indicates professional functions which are characteristic for this profession. Knowledge of professional legislation and its conscious application in professional practice is a basic obligation in the midwife’s practice. Lack of knowledge in this regard has serious legal and moral consequences, as well as might pose a risk to the patient safety. This study contains an analysis of the legislation that determine the professional functions of midwives and influence the rules of the professional performance for midwifery profession.